Conductive paste for electrolytic capacitors and electrolytic capacitors
A conductive paste with flaky metal and acicular particles in a thermosetting resin improves the joint strength and reduces ESR in electrolytic capacitors, addressing the limitations of existing adhesives by enhancing mechanical strength and conductivity.
Patent Information
- Application Number
- JP2022501836
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-02-20
- Filing Date
- 2021-02-10
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2041-02-10
AI Technical Summary
Existing conductive adhesives for electrolytic capacitors, such as those containing organic solvents like dibasic acid esters, face limitations in enhancing the connection strength between the element and terminals, and are prone to void formation due to solvent evaporation, leading to increased equivalent series resistance (ESR).
A conductive paste comprising thermosetting resin and conductive particles, including flaky metal and acicular conductive particles, is used to form a joint between the cathode part and the cathode lead terminal, which improves mechanical strength and reduces ESR by increasing contact ratio and reducing oxidation effects.
The solution enhances the joint strength and reduces ESR, while minimizing void formation and manufacturing costs, achieving a balanced combination of conductivity and mechanical integrity.
Smart Images

Figure 0007599097000004 
Figure 0007599097000001 
Figure 0007599097000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a conductive paste for an electrolytic capacitor and an electrolytic capacitor. [Background technology]
[0002] Electrolytic capacitors are used in various electronic devices because of their small equivalent series resistance (ESR) and excellent frequency characteristics. Electrolytic capacitors usually have a capacitor element with an anode part and a cathode part, an anode lead terminal electrically connected to the anode part, and a cathode lead terminal electrically connected to the cathode part. The capacitor element is usually sealed with an exterior member.
[0003] Patent Document 1 aims to provide a solid electrolytic capacitor with low ESR and excellent connection strength between the element and terminals, and proposes a solid electrolytic capacitor including a capacitor element in which a dielectric film and a cathode layer are successively formed on the surface of an anode body, and a plate-shaped terminal is attached to the capacitor element via a conductive adhesive layer, in which the conductive adhesive includes a flat-shaped conductive member and has an area in which the flat-shaped conductive member lies along the plate-shaped terminal and an area in which the flat-shaped conductive member stands in the thickness direction of the conductive adhesive layer. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2010-187016 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, there is a limit to how much the connection strength between the element and the terminal can be increased by simply incorporating a flat conductive member into the conductive adhesive as in Patent Document 1. In addition, the conductive adhesive in Patent Document 1 contains an organic solvent made of a dibasic acid ester, which makes it easy for voids to form between the element and the terminal. [Means for solving the problem]
[0006] One aspect of the present invention relates to a conductive paste for an electrolytic capacitor, comprising a thermosetting resin and conductive particles, the conductive particles including flake-like metal particles and acicular conductive particles, and connecting a cathode portion and a cathode lead terminal of an electrolytic capacitor.
[0007] Another aspect of the present invention relates to an electrolytic capacitor comprising: a capacitor element having an anode portion and a cathode portion; an anode lead terminal electrically connected to the anode portion; a cathode lead terminal electrically connected to the cathode portion; and a joint interposed between the cathode portion and the cathode lead terminal, wherein the joint includes a cured resin material and conductive particles embedded in the cured resin material, and the conductive particles include flaky metal particles and needle-shaped conductive particles. Effect of the Invention
[0008] According to the present invention, it is possible to increase the strength of the joint between the cathode part and the cathode lead terminal of an electrolytic capacitor and to achieve a good ESR. The novel features of the present invention are set forth in the appended claims, but the present invention, both in terms of structure and content, together with other objects and features of the present invention, will be better understood from the following detailed description taken in conjunction with the drawings. [Brief description of the drawings]
[0009] [Figure 1] 1 is a cross-sectional view illustrating a schematic configuration of an electrolytic capacitor according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] The conductive paste for electrolytic capacitors according to this embodiment (hereinafter also simply referred to as conductive paste) is used to connect a cathode part and a cathode lead terminal. The electrolytic capacitor comprises a capacitor element having an anode part and a cathode part, an anode lead terminal electrically connected to the anode part, a cathode lead terminal electrically connected to the cathode part, and a joint part interposed between the cathode part and the cathode lead terminal. The cathode part of the capacitor element may contain a conductive polymer. The conductive paste is used to form the joint part.
[0011] The conductive paste includes a thermosetting resin and conductive particles. The conductive particles include flake-like metal particles and needle-like conductive particles. The thermosetting resin includes all materials (mainly organic substances) that react when heated. In other words, the thermosetting resin is a concept that also includes a curing agent, a reactive diluent, and the like.
[0012] By using both flaky metal particles and needle-shaped conductive particles as conductive particles, the joint formed between the cathode part and the cathode lead terminal has low resistance and excellent mechanical strength. This is believed to be because the contact ratio between the conductive particles increases, improving conductivity, and the presence of the needle-shaped conductive particles improves the strength of the joint. As a result, a joint that can achieve high strength and low ESR can be formed between the cathode part and the cathode lead terminal of the electrolytic capacitor. In addition, since the conductive paste hardens into a film with the flaky metal particles layered on top of each other, the path for oxygen to penetrate is longer, and the impact of oxidation on the cathode part (especially the conductive polymer) is reduced. Therefore, the deterioration of the properties of the conductive polymer due to heat during the formation of the joint is reduced.
[0013] When the resistance of the joint is significantly reduced, it is possible to reduce the amount of conductive particles used. In other words, the amount of conductive particles used can be reduced and the proportion of thermosetting resin in the conductive paste can be increased, thereby further improving the mechanical strength of the joint. In addition, by reducing the amount of conductive particles used, the manufacturing cost of the conductive paste can be reduced.
[0014] The content of the conductive particles in the conductive paste may be, for example, 50% by mass or more and 70% by mass or less, or 55% by mass or more and 66% by mass or less. Here, the conductive particles may contain flaky metal particles and acicular conductive particles in a proportion of 80% by mass or more, or 90% by mass or more of the total conductive particles, or substantially all of the conductive particles (for example, 99% by mass or more) may be composed of flaky metal particles and acicular conductive particles.
[0015] The mass ratio of the flaky metal particles to the total of the flaky metal particles and the acicular conductive particles may be, for example, 60% or more and 80% or less (i.e., the mass ratio of the acicular conductive particles is 20% or more and 40% or less). When the flaky metal particles and the acicular conductive particles are used in combination at such a ratio, the contact between the conductive particles is effectively increased, so that the conductivity of the joint is significantly improved. More preferably, the mass ratio of the flaky metal particles to the total of the flaky metal particles and the acicular conductive particles may be 65% or more and 75% or less (i.e., the mass ratio of the acicular conductive particles is 25% or more and 35% or less).
[0016] More specifically, in order to effectively reduce the ESR of the electrolytic capacitor and improve the applicability of the conductive paste, the content of the flaky metal particles in the conductive paste may be 35% by mass or more and 45% by mass or less, or 38% by mass or more and 43% by mass or less. From the same viewpoint, the content of the acicular conductive particles in the conductive paste may be 12% by mass or more and 22% by mass or less, or 15% by mass or more and 20% by mass or less. When the flaky metal particles and the acicular conductive particles are contained within the above range, the resistance of the joint is significantly reduced and the applicability of the conductive paste is further improved. In this case, the content of the thermosetting resin in the conductive paste may be 33% by mass or more and 45% by mass or less, or 36% by mass or more and 43% by mass or less. This makes it easier to form a joint with higher strength.
[0017] The flaky metal particles are composed of flake-like pieces. When the thickness (minimum width) of the flaky metal particles is T, the maximum diameter (long diameter) L of the flaky metal particles as viewed in a direction parallel to the thickness T and the maximum diameter (short diameter) W perpendicular to the maximum diameter satisfy L≧W, and T is sufficiently smaller than W.
[0018] The aspect ratio L / T of the maximum diameter L to the thickness T of the flaky metal particles is, for example, 20 or more on average, and preferably satisfies 30≦L / T. Similarly, the aspect ratio W / T of the minor diameter W to the thickness T of the flaky metal particles is, for example, 20 or more on average, and preferably satisfies 30≦W / T. The average maximum diameter may be 1 μm or more and 30 μm or less, or 2 μm or more and 10 μm or less.
[0019] The thickness T, major axis L, and minor axis W of the flaky metal particles can be measured by separating the conductive particles from the conductive paste, separating the flaky metal particles and the needle-like conductive particles from the conductive particles by a method such as centrifugation, photographing 10 or more arbitrarily selected flaky metal particles with an electron microscope, and analyzing the images. For example, the major axis L of each of the photographed 10 or more flaky metal particles can be measured, and the values of the remaining middle 60% (6 if 10 particles are photographed) can be averaged to obtain the major axis L. Next, the thickness of the middle 60% of the particles can be obtained and averaged to obtain the thickness T. In addition, the aspect ratios of each of the middle 60% of the particles can be obtained and averaged to obtain the aspect ratios L / T and W / T.
[0020] The specific surface area of the flake metal particles is, for example, 1 m 2 / g or more, 5m 2 / g or less, 1.5m 2 / g or more, 3m 2 The specific surface area may be measured by measuring the specific surface area of the flaky metal particles separated in the same manner as above by the BET method.
[0021] The bulk density of the flaky metal particles is, for example, 0.3 g / cm 3 More than 1g / cm3 Less than or equal to 0.4 g / cm 3 , 0.9g / cm 3 The bulk density can be measured under conditions in accordance with JIS Z 2504.
[0022] The metal constituting the flaky metal particles is not particularly limited, but gold, silver, etc. are preferable. Among them, silver is preferable because of its excellent electrical conductivity, corrosion resistance, and cost. Silver may be the main component of the flaky metal particles. The main component refers to a component that accounts for 50% or more by mass of the flaky metal particles. Silver may account for 80% or more by mass of the flaky metal particles, or may account for 99% or more by mass.
[0023] The acicular conductive particles are composed of whisker-like linear pieces. When the fiber length of the acicular conductive particles is FL, the thickness in the direction perpendicular to the length direction at the center in the length direction is the fiber diameter D, and D is sufficiently smaller than FL.
[0024] The aspect ratio FL / D of the fiber length FL to the fiber diameter D of the acicular conductive particles is, for example, 10 or more on average, and preferably satisfies 20≦FL / D. The average fiber diameter may be, for example, 0.1 μm or more and 2 μm or less, or 0.3 μm or more and 1 μm or less. The average fiber length may be, for example, 5 μm or more and 30 μm or less, or 8 μm or more and 20 μm or less.
[0025] The fiber diameter D, fiber length FL, and aspect ratio: FL / D can be measured by photographing 10 or more randomly selected acicular conductive particles from the acicular conductive particles separated in the same manner as above with an electron microscope and analyzing the images. For example, the fiber diameter of each of the photographed 10 or more acicular conductive particles can be measured, and the maximum and minimum 20% of the distribution values are removed, and the remaining middle 60% (6 particles if 10 particles are photographed) values are averaged to obtain the fiber diameter D. Next, the fiber lengths of the middle 60% of the particles can be obtained and averaged to obtain the fiber length FL. In addition, the aspect ratios of each of the middle 60% of the particles can be obtained and averaged to obtain the aspect ratio: FL / D.
[0026] The specific surface area of the acicular conductive particles is, for example, 0.5 m 2 / g or more, 1.5m 2 / g or less, and 0.8m 2 / g or more, 1.2m 2 The specific surface area may be measured by measuring the specific surface area of the acicular conductive particles separated in the same manner as above by the BET method.
[0027] The bulk density of the acicular conductive particles is, for example, 0.5 g / cm 3 Less than or equal to 0.3 g / cm 3 The bulk density can be measured under conditions in accordance with JIS Z 2504.
[0028] The acicular conductive particles may have acicular ceramic particles and a metal coating covering at least a part of the surface of the ceramic particles. The acicular ceramic particles may be acicular crystals (whiskers) of various ceramics. By using acicular ceramic particles as the core, the strength of the acicular conductive particles themselves is significantly increased. Therefore, the mechanical strength of the joint is easily improved, and in particular, the resistance to peeling is significantly improved.
[0029] If the content of the ceramic component (core of the ceramic particle) contained in the acicular conductive particles is, for example, 20 mass % or more, the mechanical strength can be sufficiently increased. On the other hand, from the viewpoint of maintaining high electrical conductivity of the acicular conductive particles, the content of the ceramic component contained in the acicular conductive particles may be, for example, 40 mass % or less (the content of the metal coating is 60 mass % or more).
[0030] The metal constituting the metal coating is not particularly limited, but gold, silver, etc. are preferable. Among them, silver is preferable because of its excellent electrical conductivity, corrosion resistance, and cost. Silver may be the main component of the metal coating. The main component refers to a component that accounts for 50% or more by mass of the metal coating. Silver may account for 80% or more by mass, or may account for 99% or more by mass of the metal coating.
[0031] Examples of the acicular ceramic particles that can be used include potassium titanate, graphite, aluminum oxide, silicon carbide, silicon nitride, magnesium sulfate, magnesium borate, zinc oxide, and titanium boride. These may be used alone or in combination of two or more. Among these, potassium titanate is particularly preferred in terms of strength.
[0032] The conductive paste may be a solvent-free type that does not contain a solvent. In other words, the content of the solvent that can be contained in the conductive paste may be 0.1 mass % or less. A solvent refers to a component that does not participate in the reaction and volatilizes when the conductive paste is hardened.
[0033] In addition, in order to achieve a good ESR, a typical solvent-free conductive paste needs to contain conductive particles at a content of about 85% by mass. In this case, the coating property of the conductive paste is reduced and the strength of the joint is likely to be insufficient. On the other hand, if the conductive paste contains a solvent, the coating property is improved, but voids due to the solvent are formed in the joint. Since the conductive paste is cured by heating while being sandwiched between the cathode part and the cathode lead terminal, the solvent remains and voids are likely to form. The presence of voids is a factor that reduces the strength of the joint.
[0034] The thermosetting resin contains, for example, an epoxy resin and a reactive diluent. By containing a reactive diluent, it is possible to obtain a conductive paste with excellent applicability. The viscosity of the reactive diluent at 25°C is desirably, for example, 60 Pa·s or less, and may be 20 Pa·s or less. Such a low-viscosity reactive diluent plays the same role as a solvent, and can significantly improve the applicability of the conductive paste. Here, the viscosity is measured using a rotational rheometer at a shear rate of 2.5 s -1 This refers to the viscosity measured under the following conditions.
[0035] In order to improve the productivity of electrolytic capacitors, it is desirable to shorten the curing time of the thermosetting resin. In order to shorten the curing time, it is effective to reduce the viscosity of the conductive paste when it is melted. However, in order to cure the thermosetting resin in a short time, heating at a higher temperature is required. If a conductive paste containing a solvent is cured at a high temperature in a short time, the solvent will volatilize rapidly and it will be difficult to escape from between the cathode part and the cathode lead terminal, and voids will easily increase. On the other hand, a reactive diluent plays a common role with a solvent, but also reacts as a thermosetting resin to form a part of the joint, so there is no concern that voids will increase.
[0036] Considering the viscosity of the conductive paste, the reactive diluent desirably has an epoxy equivalent weight (EEW) of 50 to 400 g / eq, and more desirably 100 to 350 g / eq. Also, the reactive diluent is desirably a monofunctional or difunctional epoxy compound.
[0037] Examples of monofunctional epoxy compounds include alkyl glycidyl ethers or alkenyl glycidyl ethers, which are alcohol ethers having 3 to 15 carbon atoms, and aromatic glycidyl ethers having one phenoxy group. Examples of bifunctional epoxy compounds include alkylene glycol diglycidyl ethers and polyoxyalkylene diglycidyl ethers. More specifically, examples of the bifunctional epoxy compounds include n-butyl glycidyl ether, 2-ethylhexyl glycidyl ether, allyl glycidyl ether, higher alcohol glycidyl ether, phenyl glycidyl ether, cresyl glycidyl ether, sec-butylphenyl glycidyl ether, polyethylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, neopentyl glycol diglycidyl ether, and 1,6-hexanediol diglycidyl ether.
[0038] The thermosetting resin may contain a reactive diluent in an amount of, for example, 30 parts by mass or more and 50 parts by mass or less, or even 35 parts by mass or more and 45 parts by mass or less, per 100 parts by mass of the epoxy resin. This allows the formation of a joint having excellent application properties and strength. More specifically, in the conductive paste, the epoxy resin may be contained in an amount of, for example, 25% by mass or more and 30% by mass or less, and the reactive diluent may be contained in an amount of, for example, 9 parts by mass or more and 15 parts by mass or less.
[0039] The epoxy resin is not particularly limited, and for example, bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol AD type epoxy resin, bisphenol S type epoxy resin, fluorene type epoxy resin, naphthalene type epoxy resin, biphenyl type epoxy resin, glycidylamine type epoxy resin, alicyclic epoxy resin, dicyclopentadiene type epoxy resin, novolac type epoxy resin, polyether type epoxy resin, silicone modified epoxy resin, etc. can be used. These may be used alone or in combination of two or more. Among them, from the viewpoint of obtaining a conductive paste with good coating properties, bisphenol A type epoxy resin, bisphenol F type epoxy resin, etc. having a molecular weight of 320 or more and 400 or less are preferable, and bisphenol F type epoxy resin with less steric hindrance and low viscosity is more preferable. Examples of bisphenol A type epoxy resin include JER (registered trademark) 825, JER (registered trademark) 827, JER (registered trademark) 828, etc., manufactured by Mitsubishi Chemical Corporation. Examples of bisphenol F type epoxy resins include JER (registered trademark) 806 and JER (registered trademark) 807 manufactured by Mitsubishi Chemical Corporation.
[0040] The thermosetting resin contains a curing agent. Examples of the curing agent include phenolic resin, acid anhydride, amine compound, imidazole compound, phosphorus compound, phosphonium salt compound, bicyclic amidine, organometallic complex, urea compound of polyamine, dicyandiamide, amine adduct type aliphatic tertiary amine, microcapsule type curing agent, etc. These may be used alone or in combination of two or more. Among them, imidazole compounds are preferred, and it is more desirable to use an imidazole compound having at least one hydroxyl group (OH group) and a phenyl group directly bonded to the imidazole structure (hereinafter also referred to as "imidazole compound PH"). When the imidazole compound PH is used, it is possible to cure the thermosetting resin at a high temperature and in a short time. As a result, in addition to significantly improving the productivity of electrolytic capacitors, the ESR of the electrolytic capacitor can be further efficiently reduced. It is considered that curing the thermosetting resin containing a reactive diluent at a high temperature and in a short time increases the thermal contraction of the joint and makes it easier to increase the contact between the conductive particles.
[0041] The imidazole compound PH may be contained in the thermosetting resin in a ratio of, for example, 3 parts by mass or more and 10 parts by mass or less per 100 parts by mass of the epoxy resin and the reactive diluent in total. In the bonded portion formed after the thermosetting resin is cured, the content of the structure derived from the imidazole compound PH is, for example, about 2 to 6% by mass.
[0042] Imidazole compounds PH include 2-phenyl-4-methyl-5-hydroxymethylimidazole and 2-phenyl-4,5-dihydroxymethylimidazole. Among them, 2-phenyl-4,5-dihydroxymethylimidazole is more effective in reducing the ESR of electrolytic capacitors and improves the long-term connection reliability of the joints. The OH group of the imidazole compound PH plays a role in preventing the oxidation of conductive particles, and it is thought that the resistance of the joints is maintained low.
[0043] The conductive paste may contain general additives, for example, a silane coupling agent may be added to improve adhesion between the epoxy resin and the conductive particles, and an anionic, cationic, or nonionic dispersant may be added to improve the dispersibility of the conductive particles.
[0044] From the viewpoint of improving the productivity of electrolytic capacitors, the curing time of the thermosetting resin (i.e., conductive paste) is desirably a short time, for example, 5 minutes or less, further 2 minutes or less (preferably about 1 minute). By using the imidazole compound PH, curing in such a short time is possible. To achieve curing in a shorter time, the curing temperature may be, for example, 180°C or more and 250°C or less, or 200°C or more and 230°C or less.
[0045] Next, the electrolytic capacitor according to the present embodiment includes a capacitor element having an anode portion and a cathode portion, an anode lead terminal electrically connected to the anode portion, a cathode lead terminal electrically connected to the cathode portion, and a joint portion interposed between the cathode portion and the cathode lead terminal. Here, the joint portion includes a resin cured material and conductive particles embedded in the resin cured material, and the conductive particles include flaky metal particles and acicular conductive particles. Such an electrolytic capacitor can be obtained by forming the joint portion using the conductive paste according to the present embodiment.
[0046] The porosity of the joint is, for example, 5% by volume or less, and preferably 3% by volume or less. When the viscosity or applicability of the conductive paste is controlled by a reactive diluent, even when the conductive paste is cured at high temperature in a short time, there is almost no component that volatilizes due to heat, and voids are unlikely to form in the joint. By reducing voids, a joint with superior mechanical strength is formed.
[0047] The porosity of the joint can be calculated by taking a cross-sectional photograph of the joint (region R between the cathode and the cathode lead terminal) of the electrolytic capacitor and performing image processing such as binarization, and then calculating it as the ratio of the area of the voids to the area of region R. However, it must be at least 100,000 μm2 It is desirable to calculate the void ratio for the above region R.
[0048] The structure of the joint reflects the composition of the conductive paste. For example, the content of conductive particles in the joint is 50% by mass or more and 70% by mass or less. The content of conductive particles in the joint can be measured by disassembling the electrolytic capacitor, separating the joint to prepare a sample of the joint, and subjecting the sample to thermal analysis. More specifically, the content of conductive particles can be determined by measuring the mass of the sample that is reduced by combustion of the cured resin using a differential scanning calorimeter.
[0049] In addition, the mass ratio of the flaky metal particles to the total of the flaky metal particles and the needle-shaped conductive particles in the joint is 60% or more and 80% or less. This mass ratio can be measured by separating the residue (conductive particles) after burning the cured resin by a method such as centrifugation.
[0050] More specifically, in a preferred embodiment of the joint, the content of flake-shaped metal particles is 35% by mass or more and 45% by mass or less, the content of needle-shaped conductive particles is 12% by mass or more and 22% by mass or less, and the content of cured resin is 33% by mass or more and 45% by mass or less.
[0051] The shapes of the flaky metal particles and acicular conductive particles contained in the joint can be measured by taking a cross-sectional photograph of the joint (region R between the cathode part and the cathode lead terminal) of the electrolytic capacitor in the thickness direction and processing the image. In the cross-sectional photograph, the flaky metal particles and the acicular conductive particles can be visually distinguished.
[0052] In the cross section of the thickness direction of the joint, the flaky metal particles are oriented in a direction perpendicular to the thickness direction. Therefore, it is possible to measure the thickness of the flaky metal particles and the particle length X perpendicular to the thickness. Here, the particle length X may be regarded as the major axis L. The particle length X of any 10 or more flaky metal particles included in the cross-sectional photograph is measured, and the values of the maximum 20% and minimum 20% of the distribution are excluded, and the values of the remaining middle 60% (6 if 10 particles are photographed) are averaged. Next, the thickness of the middle 60% of the particles is calculated, and the thickness T can be calculated by averaging. In addition, the aspect ratio of each of the middle 60% of the particles is calculated, and the aspect ratio: L(X) / T can be obtained by averaging.
[0053] The needle-shaped conductive particles are more randomly oriented than the flaky metal particles. From the needle-shaped conductive particles contained in the cross-sectional photograph, 10 or more particles whose total length can be measured are arbitrarily selected, their fiber length is measured, and the maximum 20% and minimum 20% of the distribution are removed, and the remaining middle 60% (6 if 10 particles are photographed) are averaged to obtain the fiber length FL. Next, the fiber diameter of the middle 60% of the particles is obtained, and the fiber diameter D can be obtained by averaging them. In addition, the aspect ratio of each of the middle 60% of the particles is obtained, and the aspect ratio: FL / D can be obtained by averaging them.
[0054] The electrolytic capacitor may have an exterior member that seals the capacitor element and exposes a part of the anode lead terminal and a part of the cathode lead terminal. The exterior member protects the capacitor element from heat and moisture from the outside and reinforces the mechanical strength of the joint. The exterior member is composed of, for example, a cured product of an insulating thermosetting resin composition. The thermosetting resin composition contains, for example, an epoxy resin as a main component, and may contain an insulating filler such as inorganic particles.
[0055] 1 is a longitudinal sectional view showing a schematic diagram of an electrolytic capacitor according to the present embodiment. Electrolytic capacitor 200 has a substantially hexahedral outer shape including three pairs of opposing flat surfaces, and includes capacitor element 10, exterior member 50 that seals capacitor element 10, and anode lead terminal 20 and cathode lead terminal 40 that are exposed to the outside of exterior member 50.
[0056] The capacitor element 10 has a porous sintered body 11 serving as an anode body in which a part of an anode wire 12 is embedded, a dielectric layer 13 formed on the surface of the porous sintered body 11, a solid electrolyte layer 14 formed on the surface of the dielectric layer 13, and a cathode layer 15 formed on the surface of the solid electrolyte layer 14. The solid electrolyte layer 14 may contain a conductive polymer. The anode wire 12 and the porous sintered body 11 constitute an anode part. The solid electrolyte layer 14 and the cathode layer 15 constitute a cathode part.
[0057] The exposed portion 12b of the anode wire 12 protruding from the porous sintered body 11 is electrically connected to the anode lead terminal 20 by resistance welding or the like. Meanwhile, the cathode layer 15 of the cathode portion is electrically connected to the cathode lead terminal 40 via the conductive paste 30 within the exterior member 50. The anode lead terminal 20 and the cathode lead terminal 40 shown in FIG. 1 protrude from the exterior member 50 and are bent so that their lower surfaces are disposed on the same plane as the bottom surface of the exterior member 50. The lower surfaces of the anode lead terminal 20 and the cathode lead terminal 40 are used for soldering or the like to a substrate (not shown) on which the electrolytic capacitor 200 is to be mounted.
[0058] The porous sintered body 11 is, for example, a rectangular solid formed body obtained by sintering metal particles. The metal particles are made of a valve metal such as titanium (Ti), tantalum (Ta), or niobium (Nb).
[0059] The anode wire 12 is made of a conductive material. The material of the anode wire 12 is not particularly limited, and examples thereof include the valve metals mentioned above, as well as copper, aluminum, and aluminum alloys.
[0060] The dielectric layer 13 is made of, for example, a metal oxide. Examples of methods for forming a layer containing a metal oxide on the surface of the porous sintered body 11 include a method of immersing the porous sintered body 11 in a chemical conversion liquid to anodize the surface of the porous sintered body 11, and a method of heating the porous sintered body 11 in an atmosphere containing oxygen.
[0061] The solid electrolyte layer 14 is formed so as to cover at least a part of the dielectric layer 13. For example, a manganese compound or a conductive polymer is used for the solid electrolyte layer 14. Examples of the conductive polymer include polypyrrole, polythiophene, polyfuran, polyaniline, polyacetylene, polyphenylene, polyparaphenylenevinylene, polyacene, polythiophenevinylene, polyfluorene, polyvinylcarbazole, polyvinylphenol, polypyridine, or derivatives of these polymers. These may be used alone or in combination. The conductive polymer may also be a copolymer of two or more monomers. Among these, polythiophene, polyaniline, polypyrrole, etc. are preferred in terms of excellent conductivity. Among these, polypyrrole is preferred in terms of excellent water repellency.
[0062] The cathode layer 15 has, for example, a carbon layer formed so as to cover the solid electrolyte layer 14, and a metal paste layer formed on the surface of the carbon layer. The carbon layer contains a conductive carbon material such as graphite and a resin. The metal paste layer contains, for example, metal particles (e.g., silver) and a resin. Note that the configuration of the cathode layer 15 is not limited to this configuration.
[0063] The anode lead terminal 20 is electrically connected to the anode part via the anode wire 12. The material of the anode lead terminal 20 is not particularly limited as long as it is electrochemically and chemically stable and conductive, and may be either metallic or non-metallic. The shape of the anode lead terminal 20 is, for example, long and flat.
[0064] The cathode lead terminal 40 is electrically connected to the cathode part via the joint 30 which is a hardened conductive paste. The material of the cathode lead terminal 40 is not particularly limited as long as it is electrochemically and chemically stable and conductive, and may be either metallic or non-metallic. The shape of the cathode lead terminal 40 is not particularly limited as well, and may be, for example, a long, flat plate.
[0065] The exterior member 50 is formed by molding a thermosetting resin composition in a mold by, for example, transfer molding, compression molding, etc. Examples of the thermosetting resin include epoxy resin, phenol resin, silicone resin, melamine resin, urea resin, alkyd resin, polyurethane, polyimide, unsaturated polyester, etc.
[0066] The present invention will be described in detail below with reference to examples, but the present invention is not limited to the following examples.
[0067] Details of the materials used in preparing the thermosetting resin are given below. <Epoxy resin> (a) Bisphenol F type epoxy resin (EEW: 165g / eq) (b) Bisphenol A epoxy resin (EEW: 190g / eq)
[0068] <Reactive diluent> (a) 2-Ethylhexyl glycidyl ether (EEW: 205 g / eq, viscosity (25°C): 3 mPa s) (b) 1,6-Hexanediol diglycidyl ether (EEW: 117 g / eq, viscosity (25°C): 10 mPa s)
[0069] <Hardening agent> (a) 2-phenyl-4-methyl-5-hydroxymethylimidazole (b) 2,4-diamino-6-(2'-ethyl-4'-methylimidazolyl-(1'))-ethyl-s-triazine (c) Dicyandiamide (d) Amine adduct type aliphatic tertiary amine
[0070] Example 1 The following conductive particles were prepared. (Flake-like metal particles A) Silver flakes (Ag content 100%) with thickness T = 0.2 μm, maximum diameter L = 5.5 μm, and aspect ratio: L / T = 27.5
[0071] (Acicular conductive particles B) Potassium titanate whiskers (Ag content 75% by mass) with a silver coating, fiber diameter D = 0.7 μm, fiber length FL = 8 μm, and aspect ratio: FL / D = 11.4
[0072] (Thermosetting resin A) A thermosetting resin was prepared by mixing 100 parts by mass of a bisphenol F type epoxy resin (the above epoxy resin (a)), 42 parts by mass of a reactive diluent, 2-ethylhexyl glycidyl ether (the above reactive diluent (a)), and 10 parts by mass of a curing agent, 2-phenyl-4-methyl-5-hydroxymethylimidazole (the above curing agent (a)).
[0073] (Conductive paste A) Using flaky metal particles A, acicular conductive particles B and thermosetting resin A, a conductive paste A was prepared having a flaky metal particle A content of 41 mass%, a acicular conductive particle C content of 17 mass% or less and a thermosetting resin A content of 42 mass%.
[0074] Comparative Example 1 The following conductive particles were prepared. (Flake-like metal particles C) Silver flakes (Ag content 100%) with thickness T = 1 μm, maximum diameter L = 6 μm, and aspect ratio: L / T = 6
[0075] (Thermosetting resin X) Thermosetting resin X was prepared by mixing 100 parts by mass of bisphenol F type epoxy resin (the above epoxy resin (a)), 6 parts by mass of dicyandiamide (the above curing agent (c)) as a curing agent, 2 parts by mass of 2-phenylimidazole as a curing catalyst, and 35 parts by mass of diethylene glycol monoethyl ether as a solvent.
[0076] (Conductive Paste X) Using flaky metal particles C and thermosetting resin X, a conductive paste X was prepared in which the content of flaky metal particles C was 90 mass % and the content of non-volatile components (i.e., components other than the solvent) of thermosetting resin X was 10 mass %.
[0077] Comparative Example 2 (Thermosetting resin Y) Thermosetting resin Y was prepared by mixing 100 parts by mass of bisphenol F type epoxy resin (the above epoxy resin (a)), 6 parts by mass of dicyandiamide (the above curing agent (c)) as a curing agent, and 2 parts by mass of 2-phenylimidazole as a curing catalyst.
[0078] (Conductive paste Y) Using thermosetting resin Y and the same flaky metal particles C as used in Comparative Example 1, a conductive paste Y was prepared having a flaky metal particle C content of 85 mass% and a thermosetting resin Y content of 15 mass%.
[0079] [evaluation] (1)ESR An electrolytic capacitor with a rated voltage of 16 V and a rated capacitance of 100 μF was fabricated in the following manner.
[0080] (Preparation of the anode part) Tantalum metal particles having an average primary particle size D50 of approximately 0.1 μm as a valve metal were formed into a predetermined shape and then sintered to obtain a porous sintered body (anode part) in which a part of a tantalum anode wire was embedded.
[0081] (Formation of dielectric layer) The porous sintered body was immersed in a chemical conversion bath, and a dielectric layer of tantalum oxide was formed on the surface of the porous sintered body by anodization. The chemical conversion voltage was set to 60V.
[0082] (Preparation of polymer dispersion) 3,4-Ethylenedioxythiophene and polystyrene sulfonic acid (PSS, weight average molecular weight 100,000) were dissolved in ion-exchanged water, and the resulting mixed solution was stirred while iron (III) sulfate (oxidant) was added to carry out a polymerization reaction. The reaction solution was then dialyzed to remove unreacted monomers and the oxidant, yielding a polymer dispersion containing polyethylenedioxythiophene doped with approximately 5% by mass of PSS (PEDOT / PSS).
[0083] (Formation of solid electrolyte layer) The anode part was immersed in the polymer dispersion for 5 minutes in a reduced pressure atmosphere (40 kPa), and then the anode part was pulled out of the polymer dispersion. The anode part impregnated with the polymer dispersion was then dried to form a solid electrolyte layer covering at least a part of the dielectric layer.
[0084] (Cathode formation) A carbon layer was formed on the surface of the solid electrolyte layer using carbon paste, and a silver paste layer was formed by applying silver paste to the surface of the carbon layer, thus obtaining a capacitor element having a cathode portion composed of a carbon layer and a silver paste layer.
[0085] (Lead terminal joining) A lead frame with an integrated anode lead terminal and cathode lead terminal was cut out from a single aluminum foil. Next, a specific conductive paste was applied to the surface of the solid electrolyte layer and connected to the cathode lead terminal of the lead frame. Meanwhile, the exposed part of the anode wire was welded to the anode lead terminal of the lead frame. After that, the product was heated at 210°C for 1 minute to harden the conductive paste and form a joint between the cathode part and the cathode lead terminal.
[0086] (Sealing of capacitor elements) The lead frame and capacitor element were sealed in an exterior material to complete the electrolytic capacitor as shown in Figure 1. After that, aging was performed for 90 minutes at 95°C while applying the rated voltage. The ESR of the electrolytic capacitor after aging was measured. ESR below the standard value was marked "Good", ESR less than 0.5 mΩ higher than the standard value was marked "Good", and ESR 0.5 mΩ or more higher than the standard value was marked "Poor".
[0087] (2)Join strength Two aluminum pieces for tensile testing were bonded together with conductive paste and heated at 210°C for one minute to harden the conductive paste, after which the tensile strength was measured using a tension and compression testing machine from Imada Manufacturing Co., Ltd. Tensile strength equal to or greater than the standard value was marked as "Good", strength less than 2N lower than the standard value was marked as "Good", and strength 2N or more lower than the standard value was marked as "Poor".
[0088] (3) Porosity Using the method described above, the cross section of the joint of the electrolytic capacitor was photographed with an electron microscope, and the image was processed to calculate the porosity. A porosity of 5 volume percent or less was evaluated as "good", and a porosity of more than 5 volume percent was evaluated as "poor".
[0089] (4) Spreadability When the conductive paste was applied with the dispenser, the case where it could be applied without any sharp edges was rated as "good", and when stringiness or sharp edges occurred, the case where stringiness or sharp edges occurred was rated as "bad".
[0090] [Table 1]
[0091] From Table 1, it can be seen that higher bonding strength can be obtained when using conductive paste A, which combines flaky metal particles A and needle-like conductive particles B, compared to conventional solvent-type or solventless conductive pastes. It can also be seen that conductive paste A has excellent coatability, and when it is used, the porosity of the joint is reduced.
[0092] Examples 2 to 5 Conductive pastes B to E of Examples 2 to 5 were prepared in the same manner as in Example 1, except that the contents of the flaky metal particles A, the acicular conductive particles B, and the thermosetting resin A were changed as shown in Table 2.
[0093] [Table 2]
[0094] It can be seen from Table 2 that, when the conductive particles have a specified composition, better coating properties are achieved and a joint with excellent balance of physical properties can be formed.
[0095] Examples 6 to 8 Conductive pastes F to H of Examples 6 to 8 were prepared in the same manner as in Example 1, except that the composition of the thermosetting resin was changed as shown in Table 3.
[0096] <Example 6> (Thermosetting resin F) Thermosetting resin F was prepared by mixing 100 parts by mass of bisphenol F type epoxy resin (epoxy resin (a)), 42 parts by mass of 2-ethylhexyl glycidyl ether (reactive diluent (a)) as a reactive diluent, and 10 parts by mass of 2,4-diamino-6-(2'-ethyl-4'-methylimidazolyl-(1'))-ethyl-s-triazine (curing agent (b)) as a curing agent.
[0097] <Example 7> (Thermosetting resin G) Thermosetting resin G was prepared by mixing 100 parts by mass of bisphenol A type epoxy resin (epoxy resin (b)), 42 parts by mass of 1,6-hexanediol diglycidyl ether (reactive diluent (b)) as a reactive diluent, 8 parts by mass of dicyandiamide (curing agent (c)) as a curing agent, and 3 parts by mass of 2-phenylimidazole as a curing catalyst.
[0098] <Example 8> (Thermosetting resin H) A thermosetting resin was prepared by mixing 100 parts by mass of bisphenol A type epoxy resin (epoxy resin (b)), 42 parts by mass of 1,6-hexanediol diglycidyl ether (reactive diluent (b)) as a reactive diluent, and 29 parts by mass of an amine adduct type tertiary amine (curing agent (d)) as a curing agent.
[0099] [Table 3]
[0100] From Table 3, it can be seen that even when the type of reactive diluent or curing agent is changed, good application properties can be achieved and a joint with an excellent balance of physical properties can be formed. [Industrial Applicability]
[0101] The present invention can be used in electrolytic capacitors in which the anode portion comprises a porous sintered body, a metal foil, or the like, and is particularly useful in solid electrolytic capacitors having a solid electrolyte layer on the surface of a dielectric layer formed in the anode portion. Although the present invention has been described with respect to the presently preferred embodiments, such disclosure should not be interpreted as limiting. Various variations and modifications will no doubt become apparent to those skilled in the art to which the present invention pertains upon reading the above disclosure. Accordingly, the appended claims should be interpreted to cover all variations and modifications without departing from the true spirit and scope of the present invention. [Explanation of symbols]
[0102] 10: Capacitor element 12: Anode wire 12b:Exposed part 13: Dielectric layer 14: Solid electrolyte layer 15: Cathode layer 20: Anode lead terminal 30: Joint (hardened conductive paste) 40: Cathode lead terminal 50: Exterior materials 200: Electrolytic capacitor
Claims
1. A thermosetting resin and conductive particles are included, The conductive particles include flake-like metal particles and needle-like conductive particles, The thermosetting resin includes an epoxy resin, a reactive diluent, and an imidazole compound, The reactive diluent has an epoxy equivalent weight of 50 to 400 g / eq. The imidazole compound has at least one hydroxyl group and a phenyl group directly bonded to the imidazole structure, A solventless electrolytic capacitor conductive paste having a solvent content of 0.1 mass % or less, for connecting a cathode part containing a conductive polymer of an electrolytic capacitor to a cathode lead terminal.
2. 2. The conductive paste for electrolytic capacitors according to claim 1, wherein the content of the conductive particles contained in the conductive paste is 50% by mass or more and 70% by mass or less.
3. 3. The conductive paste for electrolytic capacitors according to claim 1, wherein a mass ratio of the flaky metal particles to the total of the flaky metal particles and the acicular conductive particles is 60% or more and 80% or less.
4. The content of the flaky metal particles is 35% by mass or more and 45% by mass or less, The content of the acicular conductive particles is 12% by mass or more and 22% by mass or less, The conductive paste for electrolytic capacitors according to any one of claims 1 to 3, wherein the content of the thermosetting resin is 33 mass % or more and 45 mass % or less.
5. The flaky metal particles are The aspect ratio of the maximum diameter to the thickness is, on average, 20 or more; The conductive paste for electrolytic capacitors according to any one of claims 1 to 4, wherein the average maximum diameter is 1 µm or more and 30 µm or less.
6. The needle-shaped conductive particles are The aspect ratio of the fiber length to the fiber diameter is, on average, 10 or more; The average fiber diameter is 0.1 μm or more and 2 μm or less, The conductive paste for electrolytic capacitors according to any one of claims 1 to 5, wherein the average fiber length is 5 µm or more, and 30 µm or more.
7. The conductive paste for electrolytic capacitors according to any one of claims 1 to 6, wherein the flaky metal particles are mainly composed of silver.
8. The conductive paste for electrolytic capacitors according to any one of claims 1 to 7, wherein the acicular conductive particles have acicular ceramic particles and a metal coating covering at least a portion of the surface of the ceramic particles.
9. 9. The conductive paste for electrolytic capacitors according to claim 8, wherein the metal film is mainly composed of silver.
10. 10. The conductive paste for electrolytic capacitors according to claim 8, wherein the ceramic particles are at least one selected from the group consisting of potassium titanate, graphite, aluminum oxide, silicon carbide, silicon nitride, magnesium sulfate, magnesium borate, zinc oxide, and titanium boride.
11. a capacitor element including an anode portion and a cathode portion including a conductive polymer; an anode lead terminal electrically connected to the anode portion; a cathode lead terminal electrically connected to the cathode portion; a joint portion interposed between the cathode portion and a cathode lead terminal; Equipped with The porosity of the joint is 5 volume % or less, the bonding portion includes a cured resin and conductive particles embedded in the cured resin, The conductive particles include flake-like metal particles and needle-like conductive particles, At the joint, The content of the flaky metal particles is 35% by mass or more and 45% by mass or less, The content of the acicular conductive particles is 12% by mass or more and 22% by mass or less, The content of the cured resin is 33% by mass or more and 45% by mass or less, The flaky metal particles are The aspect ratio of the grain size to the thickness is, on average, 20 or more; The average particle size is 1 μm or more and 30 μm or less, The needle-shaped conductive particles are The aspect ratio of the fiber length to the fiber diameter is, on average, 10 or more; The average fiber diameter is 0.1 μm or more and 2 μm or less, An electrolytic capacitor having an average fiber length of 5 μm or more, 30 μm or more.
12. The electrolytic capacitor according to claim 11 , wherein the flake-shaped metal particles are primarily composed of silver.
13. 13. The electrolytic capacitor according to claim 11, wherein the acicular conductive particles each include an acicular ceramic particle and a metal coating covering at least a portion of a surface of the ceramic particle.
14. 14. The electrolytic capacitor of claim 13, wherein the metal film is primarily composed of silver.
15. 15. The electrolytic capacitor according to claim 13, wherein the ceramic particles are at least one selected from the group consisting of potassium titanate, graphite, aluminum oxide, silicon carbide, silicon nitride, magnesium sulfate, magnesium borate, zinc oxide, and titanium boride.
16. 16. The electrolytic capacitor according to claim 11, further comprising an exterior member that seals the capacitor element and exposes a portion of the anode lead terminal and a portion of the cathode lead terminal.
Citation Information
Patent Citations
Conductive binder
JP1995205395A
Conductive powder and conductive composite
JP2002298654A
Elastic conductive adhesive and inter-electrode connection structure
JP2006032412A
Silver paste
JP2006049106A
Solid electrolytic capacitor and manufacturing method therefor
JP2010187016A
